Indonesian Government Diplomacy on Protecting Indonesian Migrant Workers in Papua New Guinea During COVID-19 Pandemic - Suryanti, Made Selly Dwi; Sinaga, Melpayanty (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2022)
COVID-19 Pandemic that started from the end of 2019 and developed in 2020 has changed international world order. That changed felt by all countries in the world, including Indonesia. The rapid raising of casualties made the government taking a lockdown policy. It was meant to protect their citizens and prevent a more massive spreading. That protection is not only applied for the citizens in the country but also for the citizens living abroad like Indonesian migrant workers. One particular case that became the focus of this research is the migrant workers who works in Papua New Guinea (PNG). Human right is a main instrument in protecting the citizens. That is the importance of government in this case. This research aims to analyze Indonesian diplomacy strategies in protecting the rights of migrant workers who works in PNG during the Pandemic with humanity aspect as its main concern. Method that is used in this research is a descriptive qualitative using primary and secondary data through interviews and literature study from relevant and validated sources. The result of this research shows that Indonesian Government is taking the model of protection diplomacy in protecting Indonesian migrant workers in PNG.